Character Education in the Book of Hikam and Its Relevance to National Character Education Program in Indonesia - Suhesty, Aulia; Rahayu, Diah; Lyona, Annisa; Hussain, Sajjad (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2022)
The aim of this study is to explain the concept of character education contained in the book of Hikam and its relevance to Indonesia's national character education program. This research was a library study that employed the content analysis technique. The data collection method was the documentation technique. The findings of this study indicate that the concept of character education in the book of Hikam emphasizes religious character education. This approach focuses on uluhiyyah (divinity), suggesting that humans should align all their life activities with God by spreading goodness in all circumstances. The closer and more obedient a person is to God, the more character and noble that person would be. This religious education is an exercise (riyadhah) and sincerity (mujahadah) that is well organized and systematic and carried out by an educator to shape a pious personality in a student, both physically and spiritually. The concept of religious character refers to faith, honesty, piety, sincerity, and patience. Religious character teaches human being to become a person with character and responsibility. The character education values in the book of Hikam strengthen Indonesia's national character education program. In Sheikh Ibn Atha'illah's view, the character education strategy are divided into two stages: planting and spreading. Religious education is very relevant to the national character education strategy, such as intervention (instilling character in students) and habituation (instilling character through the environment). Studi ini bertujuan menjelaskan konsep pendidikan karakter yang ada dalam kitab Sufi Hikam serta relevansinya terhadap program nasional pendidikan karakter yang ada di Indonesia. Penelitian ini adalah library research yang mengunakan teknik content analisa. Teknik pengumpulan data yang digunakan adalah teknik dokumentasi. Temuan dalam penelitian ini adalah konsep pendidikan karakter yang ada pada kitab sufi Hikam adalah pendidikan karakter religious yang mengacu pada karakter uluhiyyah (ketuhanan), yakni manusia harus mengorientasikan segala aktivitas kehidupanya kepada tuhan dengan menyebarkan kebaikan dimana saja berada. Semakin dekat dan taat seseorang kepada tuhanya maka orang tersebut akan semakin berkarakter dan berakhlak mulia. Pendidikan religius ini merupakan suatu latihan (riyadhah) dan kesungguhan (mujahadah) yang terencana dan sistematis, serta dilakukan oleh seorang pendidik untuk membentuk kepribadian yang shaleh pada seorang anak didik baik dari segi jasmani maupun rohaninya. Konsep karakter religius ini mengacu pada nilai-nilai keimanan, kejujuran, ketakwaan, keikhlasan dan kesabaran. Kitab Hikam mendidik seorang manusia menjadi pribadi yang berkarakter dan bertangung jawab. Nilai-nilai pendidikan karakter pada kitab Hikam menguatkan program nasional pendidikan karakter di Indonesia. Strategi pendidikan karakter dalam pandangan Syeikh Ibnu Atha’illah dibagi dalam dua tahap, yaitu proses penanaman dan penyebaran. Hal ini sangat relevan dengan strategi pendidikan karakter nasional, yaitu intervensi (penanaman karakter pada diri peserta didik), dan habituasi (penanaman karakter melalui lingkungan).